Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-10-27T20:36:03+01:00
A)
x⁴-4x³+x-4=0
x³(x-4)+1(x-4)=0
x³+1=0
x³=-1
∛x³=∛-1
x=-1

b)
7x²(x-2)(x+2) ≥ 0
7x²(x²-4)≥0
7x⁴-28x²≥0
nie wiem :)

c)
12x³-4x²-3x+1< 0
4x²(3x-1)-1(3x-1)<0
4x²-1<0
4x²<1 [/:4]
x²=1/4
√x²=√(1/4)²
x=1/2
1 5 1
2009-10-27T20:41:16+01:00

a.) x⁴-4x³+x-4=0
x³(x-4)+1(x-4)=0
x³+1=0
x³=-1
∛x³=∛-1
x=-1


b.)7x²(x-2)(x+2) ≥ 0
7x²(x²-4)≥0
7x⁴-28x²≥0
nie wiem :)


c.)12x³-4x²-3x+1< 0
4x²(3x-1)-1(3x-1)<0
4x²-1<0
4x²<1 [/:4]
x²=1/4
√x²=√(1/4)²
x=1/2